Circular economic engineering through technologization - Argota Pérez, Geomanis (2024)
The technologization of circular economy engineering faces barriers inadoption and training, generating social inequalities. The aim of the studywas to describe circular economic engineering from its technologization.A comprehensive review of the scientific literature was conducted toidentify and evaluate the relevance of key indicators, which were: I)technological innovation and sustainability, II) circular economy, III)socio-economic and environmental indicators, IV) technological modelof circular economy, V) challenges in developing countries, VI) role ofengineering in circular economy, and VII) social implications of circulareconomy. The results highlight the assessment of technological innovationfor sustainability; transition towards a circular economic model; positivesocio-economic and environmental impacts; cost reduction and economicopportunities; technological barriers in developing countries; crucialrole of engineering in circular systems; social implications such as jobcreation and social inclusion. It is concluded that circular economy, drivenby technological innovation, promotes process optimization, resourceefficiency, and sustainable solutions; however, barriers in technologicaladoption and training persist, indicating the need to adapt technologicalmodels and develop social competencies for an effective transition towardssustainability.